Refractory myasthenia gravis: Characteristics of a portuguese cohort - Santos, Ernestina (2020)
Introduction: Some myasthenia gravis (MG) patients are refractory to conventional treatments. Methods: To describe the clinical features of refractory MG (RMG) and explore the association with human leukocyte antigen HLA-DRB1 alleles, a cohort study of 114 consecutive MG patients was performed. Patients were classified as RMG based on predefined criteria. Results: Twenty-two patients were found to have RMG (19.3%). There were no differences between non-RMG and RMG patients with respect to sex, age of onset, abnormal 3-Hz repetitive nerve stimulation, anti-acetylcholine receptor antibody positivity, thymectomy, thymoma or thymic hyperplasia, and polyautoimmunity. HLA-DRB1*03 was more frequent in the non-RMG vs. control population (P = 3 × 10-6 ). The HLA-DRB1*13 allele was less frequent in non-RMG patients compared with controls (P = 0.002), and less frequent in the non-RMG group compared with the RMG group (P = 0.003). Discussion: HLA-DRB1*03 was more common in non-RMG, and the HLA-DRB1*13 allele appeared to have a protective role, as reported previously in other autoimmune disorders. Muscle Nerve 60: 188-191, 2019.